Self-regeneration of neuromuscular function following soman and VX poisoning in spinal cord—skeletal muscle cocultures. (26th February 2016) - Weimer, Isabel; Worek, Franz; Seeger, Thomas; Thiermann, Horst; Eckle, Veit‑Simon; Grasshoff, Christian; Antkowiak, Bernd
Highlights: Neuromuscular signs of OP poisoning in vivo manifest in nerve-muscle cocultures. Recovery of muscular function was evident 3 d and 7 d after intoxication with nerve agents. Cocultures may serve as test system to investigate long term effects of nerve agent intoxication. Abstract: Aside from nerve agents, various highly toxic pesticides belong to the group of organophosphorus (OP) compounds, thereby causing a large number of intoxications every year. Unfortunately, there are still shortcomings in the current treatment for OP poisoning and research on novel therapeutic options is restricted in several aspects. In this study we investigated the suitability of organotypic cocultures for pharmacological in vitro studies involving OP compounds. These slice cultures are derived from murine spinal cord and muscle tissue forming functional neuromuscular synapses, which trigger spontaneous contractions of muscle fibers. Using video microscopy to quantify muscle activity, we assessed the viability of cocultures after exposure to soman and VX, and the associated loss and recovery of neuromuscular function. Antidotal treatment was not provided. The application of nerve agents led to an almost complete loss of muscle activity. However, cell cultures regained equivalent muscular function to the control situation three and seven days after intoxication. In summary, the tested in vitro system could be a promising tool for the investigation of long term effects and therapeutic options for OP poisoning.